The Application of Leadership Style in Creating a Conducive Work Culture: A Case Study of Bonebone Sub-District - Siradja, Noor Gemilang; Rusli, Andi M.; Syamsu, Suhardiman (Glocal Society Journal, 2024)
This study aims to analyze the application of the Sub-District leadership style in creating a conducive work culture in Bonebone Sub-District, as well as identify its supporting and inhibiting factors. Using a qualitative approach, data was collected through interviews, observations, and doscumentation. The results showed that the Sub-District head applied a participatory and consultative leadership style as dominant. This style has proven to be effective in building cooperation between staff, increasing motivation, and creating transparent communication. Supporting factors include the provision of facilities and infrastructure, the implementation of regular meetings, and strong team collaboration. On the other hand, the obstacles found include less than optimal work facilities and low motivation and discipline of staff. This study recommends the development of an e-system to improve the efficiency of public services and regular training to strengthen staff competencies. The results of the study are expected to be a reference for leadership development at the Sub-District level, especially in areas with similar characteristics. With a more adaptive and innovative approach, a conducive work culture can be more easily achieved, supporting the improvement of overall organizational performance.